Evaluation of maternal and perinatal characteristics on childhood lymphoma risk: A population‐based case‐control study. Issue 5 (28th November 2016) - Peckham‐Gregory, Erin C.; Danysh, Heather E.; Brown, Austin L.; Eckstein, Olive; Grimes, Amanda; Chakraborty, Rikhia; Lubega, Joseph; McClain, Kenneth L.; Allen, Carl E.; Scheurer, Michael E.; Lupo, Philip J.
Abstract: Background: Lymphoma is one of the most common pediatric malignancies; however, there are few well‐established risk factors. Therefore, we investigated if maternal and perinatal characteristics influenced the risk of childhood lymphoma. Procedure: Information on cases (n = 374) diagnosed with lymphoma and born in Texas for the period 1995–2011 was obtained from the Texas Cancer Registry. Birth certificate controls were randomly selected at a ratio of 10 controls per 1 case for the same period of 1995–2011. Unconditional logistic regression was used to generate unadjusted (OR) and adjusted odds ratios (aOR) and 95% confidence intervals (CI) for the following histologic subtypes: Hodgkin (HL), Burkitt (BL), and non‐BL non‐HLs (non‐BL NHLs). Results: Overall, our findings indicate specific maternal and perinatal characteristics influence childhood lymphoma risk. Mexico‐born mothers were more likely to have offspring who developed BL compared to mothers born in the United States (U.S.; aOR: 2.15; 95% CI: 1.06–4.36). Further, mothers who resided at time of delivery in a county on the U.S.‐Mexico border were more likely to give birth to offspring who developed non‐BL NHL (aOR: 1.72; 95% CI: 1.11–2.67) compared to mothers not living on the U.S.‐Mexico border at time of infant birth. Last, infants born large‐for‐gestational‐age experienced a twofold increase in BL risk (aOR: 2.00; 95% CI: 1.10–3.65). Conclusions: In this population‐based assessment, we confirmed previously reported risk predictors of childhood lymphoma, including sex of infant, while highlighting novel risk factors that warrant assessment in future studies.